2004
DOI: 10.4028/www.scientific.net/kem.259-260.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphite Intercalation Compounds Prepared by Molten Salts Method on High-Pressure Synthetic B-Doped Diamond

Abstract: B-doped diamond abrasive is an excellent grinding material owing to its high oxidation resistance, mechanical strength and inertness with ferrous metal. This paper presents a new method for synthesis of B-doped diamond grits using graphite intercalation compounds (GICs) prepared by molten salts method. GICs refer to the compounds that form through intercalating other atoms, ions or molecules into graphite planar layers. H 3 BO 3 -GICs were prepared through the reaction of graphite with molten boric acid in vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The details were introduced in the references [14]. X-ray fluorescence results confirmed that the boron content in the diamond reached about 3.75 9 10 20 cm -3 .…”
Section: Fabrication Of B-doped Pcd Electrodesupporting
confidence: 64%
See 1 more Smart Citation
“…The details were introduced in the references [14]. X-ray fluorescence results confirmed that the boron content in the diamond reached about 3.75 9 10 20 cm -3 .…”
Section: Fabrication Of B-doped Pcd Electrodesupporting
confidence: 64%
“…Previous work in our research group has presented a method to synthesize BDD crystals under the conditions of high pressure and high temperature using boron-doped graphite intercalation compounds (GICs) as carbon sources [14,15]. We have also investigated the electrochemical behavior of BDD powder electrode in the neutral supporting electrolyte and the solution containing K 3 Fe(CN) 6 / K 4 Fe(CN) 6 redox couple [16].…”
Section: Introductionmentioning
confidence: 98%
“…Synthesis of B-doped Conductive Diamond. B-doped diamond was synthesized using B-doped GICs with the mixed stages of 1~5 as carbon sources which was introduced in reference [6]. The powders of GICs were mixed with metal catalyst powders and assembled in the pyrophyllite high-pressure mould.…”
Section: Methodsmentioning
confidence: 99%